2012
DOI: 10.1149/2.045209jes
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pulse-Reverse Electrodeposited Cu Thin Films

Abstract: One of the main concerns in fabricating Cu interconnections is a significant increase in resistivity. Thus, pulse-reverse electrodeposition was implemented in an attempt to improve the properties of Cu films. The influences of the anodic step in pulse-reverse electrodeposition were intensively investigated by varying the anodic potential and time (the amount of anodic charge). It was confirmed that the anodic step affected the grain size as well as surface roughness and the change rates of these properties wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Organic additives have been extensively employed in Cu electrodeposition to control the properties of deposited Cu films. [1][2][3][4][5][6][7][8][9][10][11][12] Organic additives can be classified as accelerators, suppressors, and levelers in accordance with their influence on the electrochemical behaviors and film properties. [13][14][15] Table I shows the chemical structures of typical additives belonging to each group.…”
mentioning
confidence: 99%
“…Organic additives have been extensively employed in Cu electrodeposition to control the properties of deposited Cu films. [1][2][3][4][5][6][7][8][9][10][11][12] Organic additives can be classified as accelerators, suppressors, and levelers in accordance with their influence on the electrochemical behaviors and film properties. [13][14][15] Table I shows the chemical structures of typical additives belonging to each group.…”
mentioning
confidence: 99%
“…It was observed that the surface roughness of the Cu-Ag film was higher than that of Cu, even though the Cu-Ag film consisted of even smaller grains, which was contributed by the formation of a relatively large groove composed of a few surface grains. 35 The electrical conductivity of Cu, Cu-Ag, and Ag films is presented in Fig. 12a.…”
Section: Resultsmentioning
confidence: 99%
“…2e, 2h, 2i, 2l and 2m). 25,26 To quantitatively compare the superfilling performance, the height of Cu deposit from the bottom of the trench was used. The average height could represent the superfilling performance, because the total deposition amount was precisely controlled to 250 mC/cm 2 .…”
Section: Resultsmentioning
confidence: 99%